Pengaruh Penggunaan Teknologi Informasi, Keahlian Pemakai, dan Intensitas Pemakaian terhadap Kualitas Informasi Akuntansi dengan Budaya Organisasi sebagai Variabel Moderasi - Silka Gusdian; Tertiarto Wahyudi; Hasni Yusrianti (Jurnal Informatika Ekonomi Bisnis, 2024)
The aim of this research is to analyze the influence of the use of information technology, user expertise, and intensity of use on the quality of accounting information with organizational culture as a moderating variable in the Palembang city regional work unit (SKPD). The sample for this research was 266 respondents as government employees in SKPD Palembang City. Data was collected through a questionnaire and obtained 167 respondents. Data analysis in this research uses a PLS-based Structural Equation Modeling (SEM) approach using Smartpls. The tests carried out are convergent validity test, validity and reliability test, discriminant validity test, R-Square test. To test the hypothesis, the data from the research questionnaire were analyzed using bootstrapping calculations. The research results show that the use of information technology, user expertise, and intensity of use have a positive effect on the quality of accounting information. Meanwhile, organizational culture cannot moderate the use of information technology, user expertise, and intensity of use on the quality of accounting information. The implication of this research is that it can provide practical benefits for regional work units in the city of Palembang. Another implication is to support the theory of reason action in the study.